Crypto-currency bubbles: an application of the Phillips–Shi–Yu (2013) methodology on Mt. Gox bitcoin prices - Cheung, Adrian; Roca, E.; Su, J. (Routledge, 2015)
The creation of bitcoin heralded the arrival of digital or crypto-currency and has been regarded as a phenomenon. Since its introduction, it has experienced a meteoric rise in price and rapid growth accompanied by huge volatility swings, and also attracted plenty of controversies which even involved law enforcement agencies. Hence, claims abound that bitcoin has been characterized by bubbles ready to burst any time (e.g. the recent collapse of bitcoin’s biggest exchange, Mt Gox). This has earned plenty of coverage in the media but surprisingly not in the academic literature. We therefore fill this knowledge gap. We conduct an econometric investigation of the existence of bubbles in the bitcoin market based on a recently developed technique that is robust in detecting bubbles – that of Phillips et al. (2013a). Over the period 2010–2014, we detected a number of short-lived bubbles; most importantly, we found three huge bubbles in the latter part of the period 2011–2013 lasting from 66 to 106 days, with the last and biggest one being the one that ‘broke the camel’s back’ – the demise of the Mt Gox exchange.